2020
DOI: 10.1002/jgm.3254
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA CASC19 facilitates non‐small cell lung cancer cell proliferation and metastasis by targeting the miR‐301b‐3p/LDLR axis

Abstract: Background: Non-small cell lung cancer (NSCLC) is a lethal tumor resulting in a large number of cancer-related deaths globally. Long noncoding RNAs (lncRNAs) may modulate tumor initiation and metastasis. Although dysregulation of lncRNA cancer susceptibility 19 (CASC19) is validated in NSCLC, further exploration of the CASC19-regulated mechanism in NSCLC is still needed. Methods: CASC19 expression was examined in NSCLC cells by a quantitative reverse transcriptase-polymerase chain reaction. The specific role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…In addition, CASC19 also has an oncogenic effect on NSCLC. Wang et al found that CASC19 could bind with miR-301b-3p to regulate the expression of low-density lipoprotein receptor (LDLR), which promotes NSCLC cell proliferation and metastasis [ 47 ]. The LINC01977 is a novel carcinogenic promoter reported in breast cancer (BC).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CASC19 also has an oncogenic effect on NSCLC. Wang et al found that CASC19 could bind with miR-301b-3p to regulate the expression of low-density lipoprotein receptor (LDLR), which promotes NSCLC cell proliferation and metastasis [ 47 ]. The LINC01977 is a novel carcinogenic promoter reported in breast cancer (BC).…”
Section: Discussionmentioning
confidence: 99%
“…P < 0.05 was supposed as statistically significant. [14][15][16], but its role in OA keeps unknown. To probe whether CASC19 is altered in OA, RT-qPCR assay was conducted to test CASC19 expression in OA tissues, and the results indicated that CASC19 exhibited higher expression in OA samples (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With the fast development of science and technology, an increasing number of lncRNAs have been identified as crucial regulators in various diseases [27,28]. CASC19 has been uncovered to be implicated in various cancers [14][15][16], but its function in OA remains indistinct. In this work, CASC19 exhibited higher expression in OA tissues and cell model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study revealed that LINC00942 acts as an oncogene that promotes cell proliferation and colony formation and inhibits cell apoptosis, subsequently elevating METTL14-mediated m6A methylation levels in breast cancer initiation and progression by LNC942-METTL14-CXCR4/CYP1B1 signaling axis [31]. The lncRNA CASC19 was widely reported and markedly upregulated in multiple tumor tissues and cells, higher CASC19 expression is associated with tumor progression and poorer prognoses, including colorectal cancer, advanced gastric cancer, non-small lung cancer cells, and pancreatic cancer [32][33][34][35]. Two other studies revealed that a high expression level of CASC19 was positively correlated with radio resistance in cervical cancer and nasopharyngeal carcinoma [36,37].…”
Section: Discussionmentioning
confidence: 99%